2018
DOI: 10.1016/j.cbpa.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling vasotocinergic, isotocinergic and stress pathways after food deprivation and high stocking density in the gilthead sea bream

Abstract: The influence of chronic stress, induced by food deprivation (FD) and/or high stocking density (HSD), was assessed on stress, vasotocinergic and isotocinergic pathways of the gilthead sea bream (Sparus aurata). Fish were randomly assigned to one of the following treatments: (1) fed at low stocking density (LSD-F; 5kg·m); (2) fed at high stocking density (HSD-F, 40kg·m); (3) food-deprived at LSD (LSD-FD); and (4) food-deprived at HSD (HSD-FD). After 21days, samples from plasma, liver, hypothalamus, pituitary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 65 publications
(106 reference statements)
2
13
0
Order By: Relevance
“…The expression of glucocorticoid receptors and heat shock proteins is altered when seabass are chronically stressed by high rearing density ( 71 , 73 ). Changes in the expression of stress-related genes have also been reported in seabream exposed to different rearing densities ( 33 ) or to unpredictable chronic low intensity stress in the early stages of life ( 74 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The expression of glucocorticoid receptors and heat shock proteins is altered when seabass are chronically stressed by high rearing density ( 71 , 73 ). Changes in the expression of stress-related genes have also been reported in seabream exposed to different rearing densities ( 33 ) or to unpredictable chronic low intensity stress in the early stages of life ( 74 ).…”
Section: Discussionmentioning
confidence: 94%
“…These species constitute the largest portion (approximately 90–95%) of the Mediterranean aquaculture production, and have high economic and societal value. They, however, show often enigmatic differences in their physiology ( 27 ), especially the responsiveness and susceptibility to stress ( 28 ) and react differently to an acute stressor, when previously exposed to chronic (crowding) stress ( 29 33 ). Moreover, seabream seems more resilient than seabass in terms of growth under stress ( 31 , 32 , 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Avt and Crh sinergize to stimulate Acth release in trout pituitary in vitro , suggesting a role of Avt in the central regulation of the HPI axis. Moreover, previous studies in S. aurata highligthed a possible role of vasotocinergic and isotocinergic systems in chronic stress situations produced by high stocking densities (Mancera et al, 2008 ; Skrzynska et al, 2018 ), hyper- and hypo-osmotic transfers (Martos-Sitcha et al, 2013 , 2014a ), cortisol treatment (Kalamarz-Kubiak et al, 2014 ; Cádiz et al, 2015 ), or food-deprivation and refeeding (Skrzynska et al, 2017 ). In our present study, gene expression profiling of both hypothalamic Avt and It precursors ( avt and it , respectively) and their specific receptors ( avtrv1, avtrv2 , or itr ) were assessed in control and air-exposed sea breams.…”
Section: Discussionmentioning
confidence: 96%
“…Different endocrine and metabolic pathways have been previously studied in gilthead sea bream ( Sparus aurata ) under different chronic stress situations (Tort et al, 2011 ; Martos-Sitcha et al, 2016 ). The involvement of Avt and/or It, under different stocking densities, fasting conditions or salinity challenges, has been shown for this fish species (Sangiao-Alvarellos et al, 2006 ; Mancera et al, 2008 ; Martos-Sitcha et al, 2013 , 2014a ; Skrzynska et al, 2017 , 2018 ), as well as in others teleosts (Fryer and Leung, 1982 ; Haruta et al, 1991 ; Gilchriest et al, 2000 ). In addition, the physiological role of several endocrine players has also been assessed in different fish species under acute stressors, including air exposure, handling, or hypoxia (Arends et al, 1999 ; López-Patiño et al, 2014 ; Vera et al, 2014 ; Martos-Sitcha et al, 2018 ).…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, some studies demonstrated the lack of a direct relationship between primary and secondary responses (Iversen et al., ; Park et al., ), and under long‐term stressful conditions, other hormones could exert both stress and metabolic regulation. Arginine vasotocin (Avt), a neurohypophysial hormone in non‐mammalian vertebrates that presents a pleiotropic function in both stress and metabolic pathways of teleosts, may be another important player mediating metabolic and stress adaptation (Martos‐Sitcha, Wunderink, Gozdowska, Mancera, & Martínez‐Rodríguez, ; Sangiao‐Alvarellos et al., ; Skrzynska, Martos‐Sitcha, Martínez‐Rodríguez, & Mancera, ; Skrzynska et al., ), as the hypothalamic neurons responsible for the synthesis and release of Avt also innervate the adenohypophyseal cells from the HPI axis (Moons, Cambre, Batten, & Vandesande, ). In addition to increasing lactate levels in the control group, HD also reduced hepatic glycogen storage in all diets tested, indicating the activation of glycogenolytic processes to increase the supply of glucose due to energy expenditure resulting from HD condition.…”
Section: Discussionmentioning
confidence: 99%